Assessment of Using 99Mo and 99mTc Isotopes in Kuwait Medical Sector. Issue 4 (April 2016) - Ali, Naser
Abstract : Abstract: The Ministry of Health (MOH) in the state of Kuwait currently depends on importing the radioisotope molybdenum (Mo) in its isotopic form ( 99 Mo) to fulfill its demands. The present study was conducted on all nuclear medicine departments in the state of Kuwait. Daily, weekly, and monthly data were analyzed to statistically determine the current and future demands for the isotope 99m Tc. This analysis was performed by collecting and analyzing data on MOH consumption of 99m Tc for different diagnostic applications. The overall results indicate a partial decrease of 1.012% in the overall total demand for 99m Tc up to the year 2018 for the state of Kuwait.